Simultaneous Determination of Five Components in Aster tataricus by Ultra Performance Liquid Chromatography–Tandem Mass Spectrometry - Yang, Haotian (J Chromatogr Sci, 2016)
A novel quantitative method using high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry was developed for simultaneous determination of the important active constituents including shionone, luteolin, quercetin, kaempferol and ferulic acid in Aster tataricus from different habitats. The separation was performed on a C(18) column with acidified aqueous acetonitrile gradients. Quantification of the analytes was achieved by the use of a hybrid quadrupole spectrometer. Multiple reaction monitoring scanning was employed with positive and negative modes at the same time in a single run. The validated results of the method indicated that the method was simple, rapid, specific and reliable. The results demonstrated that the quantitative difference in content of five active compounds was useful not only for chemotaxonomy of numerous samples from different sources but also for the standardization and differentiation of several similar samples. It was the first time to report a UPLC–ESI-MS-MS method for determination of five components in A. tataricus extract. Simultaneous quantification of bioactive components by UPLC–ESI-MS could be a well-acceptable strategy to control the quality of A. tataricus extract comprehensively.